Design of a sensitive balloon sensor for safe human–robot interaction - Kim, Dongjin; Han, Seungyong; Kim, Taewi; Kim, Changhwan; Lee, Doohoe; Kang, Daeshik; Koh, Je Sung (Sensors, 2021)
As the safety of a human body is the main priority while interacting with robots, the field of tactile sensors has expanded for acquiring tactile information and ensuring safe human–robot interaction (HRI). Existing lightweight and thin tactile sensors exhibit high performance in detecting their surroundings. However, unexpected collisions caused by malfunctions or sudden external collisions can still cause injuries to rigid robots with thin tactile sensors. In this study, we present a sensitive balloon sensor for contact sensing and alleviating physical collisions over a large area of rigid robots. The balloon sensor is a pressure sensor composed of an inflatable body of low‐density polyethylene (LDPE), and a highly sensitive and flexible strain sensor laminated onto it. The mechanical crack‐based strain sensor with high sensitivity enables the detection of extremely small changes in the strain of the balloon. Adjusting the geometric parameters of the balloon allows for a large and easily customizable sensing area. The weight of the balloon sensor was approximately 2 g. The sensor is employed with a servo motor and detects a finger or a sheet of rolled paper gently touching it, without being damaged.
Keywords: Contact sensing; High sensitivity; Inflatable bodies; Robot interactions; Strain sensors; Tactile information; Tactile sensors; Without being damaged; Aircraft; Fingers; Humans; Robotics; Touch; Human–robot interaction; Pressure sensor; Soft robot